2008
DOI: 10.1002/art.23403
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of vasoactive intestinal peptide and its functional receptors in human osteoarthritic and rheumatoid synovial fibroblasts

Abstract: Objective. Vasoactive intestinal peptide (VIP) hasshown potent antiinflammatory effects in murine arthritis and ex vivo in human rheumatoid arthritis (RA) synovial cells. To investigate the potential endogenous participation of this system in the pathogenesis of RA, we analyzed the expression and regulation of VIP and its functional receptors in human fibroblast-like synoviocytes (FLS) from patients with osteoarthritis (OA) and patients with RA.Methods. The expression of VIP was studied by reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 43 publications
4
71
0
1
Order By: Relevance
“…Similar results have been published in alveolar cells where both VIP and PACAP were able to decrease the expression of certain MMPs and reduced the activation and expression of caspase3 [ 69 ]. It is also important to note that VIP and its receptors in synovial fi broblasts [ 70 ] are able to regulate infl ammatory factors release [ 71 ]. These data all strongly suggest that PACAP is a promising future therapeutic agent in infl ammatory and degenerative joint diseases [ 72 ].…”
Section: Pacap and Vip Regulates Chondrogenic Differentiationsupporting
confidence: 77%
“…Similar results have been published in alveolar cells where both VIP and PACAP were able to decrease the expression of certain MMPs and reduced the activation and expression of caspase3 [ 69 ]. It is also important to note that VIP and its receptors in synovial fi broblasts [ 70 ] are able to regulate infl ammatory factors release [ 71 ]. These data all strongly suggest that PACAP is a promising future therapeutic agent in infl ammatory and degenerative joint diseases [ 72 ].…”
Section: Pacap and Vip Regulates Chondrogenic Differentiationsupporting
confidence: 77%
“…Here we showed that the effect of LPS on VPAC2 expression occurred only in pSS but not in normal monocytes, and that it averaged a threefold increase, in line with previous observations in murine macrophages. Interestingly, a higher expression of VPAC2 was observed on fibroblast-like synovial cells from rheumatoid arthritis patients compared with osteoarthritis patients [48], suggesting that receptor differential expression might regulate VIP local effects in vivo. The increased expression of VPAC2 receptors in resting pSS monocytes shown here might reflect a compensating mechanism operating in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…After three passages, residual contamination by macrophages was avoided, previously assessed by flow cytometry analysis of SF with a purity of 95%. 19 Monocultures of SF were used for experiments until passage 8. Despite the use of cells at varying passage numbers, all comparisons within a same experimentation were made on SF at an identical passage number and at 80% to 90% confluence.…”
Section: Patients and Synovial Fibroblast Culturesmentioning
confidence: 99%
“…For relative quantification, results were presented as the relative expression with respect to the untreated condition using the formula 2 ÀDDCt , as previously described. 19 …”
Section: For Adamts Gene Expressionmentioning
confidence: 99%